Cylindromicin from Arctic-Derived Fungus Tolypocladium sp. SCSIO 40433 - Khan, Imran (Molecules, 2021)
The fungus strain SCSIO 40433 was isolated from an Arctic-derived glacier sediment sample and characterized as Tolypocladium cylindrosporum. A new compound, cylindromicin (1), and seven known secondary metabolites (2–8) were isolated from this strain. The chemical structures of these compounds were elucidated by comprehensive spectroscopic analyses. Cylindromicin (1) featured a 3,4-dihydro-2H-pyran skeleton. The absolute configuration of compound 1 was assigned via interpretation of key Nuclear Overhauser Effect Spectroscopy (NOESY) correlations and Electronic Circular Dichroism (ECD) calculation. Cylindromicin (1) exhibited significant tyrosinase inhibition activity. This study highlights Polar fungi as a potential resource for new bioactive natural products.